Vonoprazan and proton pump inhibitors: Which is superior for Helicobacter pylori eradication? - Ozercan, Mubin; Tawheed, Ahmed; Ismail, Alaa; Amer, Mohab Sherif; El-Kassas, Mohamed (Baishideng Publishing Group Inc, 2025)
Helicobacter pylori is a worldwide health problem; therefore, eradicating this bacterium is important for the health and economic status of the whole world. There are a variety of anti-secretory and antibiotic combinations for this purpose; however, antibiotic resistance is a major barrier to achieving an appropriate eradication rate (> 90%). Blockage of gastric acid is the main supportive factor of the antibiotic effect on bacteria. Therefore, anti-secretory therapy with high efficacy and safety profiles should be used in eradication regimens. Vonoprazan (VPZ), a member of the potassium competitive acid blockers, is a novel agent with a potent anti-secretory effect. The present study aimed to summarize comparative and safety studies of VPZ and proton pump inhibitors (PPIs), especially the efficacy on Helicobacter pylori eradication. VPZ was reported to have a higher efficacy and safety profile in most studies that compared VPZ-based and PPI-based regimens for eradication therapy. Despite its greater cost, the effectiveness of VPZ emerges as a viable and cost-effective alternative to PPI on gastric acid-related pathologies.
Keywords: Vonoprazan; Proton pump inhibitors; Helicobacter pylori; Potassium competitive acid blockers; Acid-related disorders